9. Nacionalna konferenca o varnosti v lokalnih skupnostih: Varnost v lokalnih skupnostih – dobre prakse, aktualne teme in raziskovanje varnosti v lokalnih skupnostih v zadnjem desetletju (University of Maribor Press, 2023)
9th National Conference on Local Safety and Security: Local Safety and Security – Good Practice, Topical Issues and Research on Safety and Security in the Past Decade. Conference proceedings comprise peer-reviewed papers presented at the 9th National Conference on Safety and Security in Local Communities, which took place in Kranj in November 2023. Safety and security in local communities remain the main topic of the conference, with a special focus of this year’s conference on good practice, topical issues, and research in the last decade. Papers present the result of the research programme Safety and Security in Local Communities – Comparison of Rural and Urban Environments of the Faculty of Criminal Justice and Security, University of Maribor and collaboration with researchers from the National Institute of Public Health, Research Centre of the Slovenian Academy of Sciences and Arts and the University of Nova Gorica, and practitioners from the police and local communities. Papers focus on various aspects of ensuring safety and security and the perception of threats in local communities, the role of modern technologies in ensuring security, problems of drugs and addiction, migration and integration of immigrants, juvenile delinquency, legal regulation of ensuring safety and security in local communities, environmental crime, residents’ perception of police and the legitimacy of police. In addition papers present examples of good practices.